2018
DOI: 10.1016/j.nicl.2018.05.031
|View full text |Cite
|
Sign up to set email alerts
|

SPG11 mutations cause widespread white matter and basal ganglia abnormalities, but restricted cortical damage

Abstract: SPG11 mutations are the major cause of autosomal recessive Hereditary Spastic Paraplegia. The disease has a wide phenotypic variability indicating many regions of the nervous system besides the corticospinal tract are affected. Despite this, anatomical and phenotypic characterization is restricted. In the present study, we investigate the anatomical abnormalities related to SPG11 mutations and how they relate to clinical and cognitive measures. Moreover, we aim to depict how the disease course influences the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 48 publications
10
56
2
Order By: Relevance
“…To measure cortical thickness, we used FreeSurfer, an automatic segmentation-based post-processing algorithm with advantages over VBM (25). Our findings are consistent with those of Faber et al (26), who found decreased cortical thickness in the precentral and paracentral motor cortices, superior parietal cortices, superior temporal gyrus, and cingulate cortices in SPG11-HSP, which suggests that SPG4-HSP and SPG11-HSP have similar cortical mechanisms. However, Rezende et al (15) did not find cortical thinning in SPG4-HSP on FreeSurfer analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To measure cortical thickness, we used FreeSurfer, an automatic segmentation-based post-processing algorithm with advantages over VBM (25). Our findings are consistent with those of Faber et al (26), who found decreased cortical thickness in the precentral and paracentral motor cortices, superior parietal cortices, superior temporal gyrus, and cingulate cortices in SPG11-HSP, which suggests that SPG4-HSP and SPG11-HSP have similar cortical mechanisms. However, Rezende et al (15) did not find cortical thinning in SPG4-HSP on FreeSurfer analysis.…”
Section: Discussionsupporting
confidence: 88%
“…VBM also showed significantly decreased gray-matter volume in the thalamus and lentiform nuclei in SPG11-HSP (27). Using the T1-MultiAtlas tool, Faber et al (26) found significantly decreased thalamus, accumbens nucleus, putamen, substantia nigra, amygdala, and red nucleus volumes in SPG11-HSP. These findings are consistent with our results of FIRST analysis, which demonstrated extensive deep gray-matter abnormality.…”
Section: Discussionmentioning
confidence: 96%
“…The 22 patients described belonged to 14 families; seven harbored homozygous mutations, and seven were compound heterozygous (details in Table ) . Eleven of the 22 patients were men.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is provided by DBS surgery, which promotes symptomatic improvement in PD patients through inhibition of the thalamus or globus pallidus internus. SPG11 is indeed characterized by widespread deep gray matter damage …”
Section: Discussionmentioning
confidence: 99%
“…Upon further investigation, we found that the spinal cord of SPG5 patients was atrophied but without correlation to the extent of disability or duration of disease, as reported for other subtypes of HSP (14). The lack of correlation may be partially explained by slow progression of SPG5 and low sensitivity of the imaging biomarker (spinal cord area).…”
Section: Discussionmentioning
confidence: 48%